El Sistema de Finito en la cláusula del bribri de Coroma según la gramática sistémico-funcional - Pacchiarotti, Sara (Journal of Philology and Linguistics of the University of Costa Rica, 2013)
This article seeks to analyze the subsystems that constitute the system of FINITENESS in Bribri in the frame of systemic-functional grammar of M.A.K. Halliday. Starting from the description of each subsystem, the author seeks to build a possible system of FINITENESS for the Bribri language. The issue of diminished transitivity in perfective negative clauses is also addressed from a systemic-functional perspective.